Cynicism and magic: Finding freedom on the Buddhist path - Trungpa, Chögyam (Shambhala, 2021)
Illustrations -- Foreword by Diana Mukpo -- Foreword by Charles Lief -- Foreword by Nikko Odiseos -- Editor's Note --Introduction -- 1. Be Cynical -- 2. Things as They Are -- 3. Our Basic Stupidity -- 4. Surrender -- 5. Karma -- 6. The Narrow Path and the Open Path -- 7. Borrowing the Buddha's Heart -- 8. Zen and Sanity -- 9. The Fourth Moment -- 10. Poetry and Song -- 11. Freedom -- 12. Magic -- Afterword -- Acknowledgments -- Books by Chögyam Trungpa -- About the Author -- Index.